Analisis Program Pembangunan dan Pemberdayaan Masyarakat (Probebaya) dalam Meningkatkan Kesejahteraan Masyarakat (Studi Kasus di Kelurahan Pelita Kecamatan Samarinda Ilir Kota Samarinda) - Irdiansyah, Irdiansyah; Sutrisno, Sutrisno; Rahayu, Vitria Puri; Reza, Reza (Peneliti.net, 2025)
Probebaya is a local government program in Samarinda City aimed at implementing development and community empowerment activities at the sub-district level, based on neighborhood units (RT), as an effort to improve community welfare. The purpose of this study is to examine the role of the Probebaya development and community empowerment program in enhancing the welfare of the community in Pelita Sub-district, Samarinda Ilir District, Samarinda City. This research is a descriptive study with a qualitative approach. Data collection was conducted through interviews with nine informants in Pelita Sub-district. The data analysis methods used include data reduction, data presentation, and verification/conclusion drawing. The findings of this study indicate that the Probebaya development and community empowerment program has played an optimal role in improving community welfare in Pelita Sub-district, Samarinda Ilir District, Samarinda City through several aspects. First, it helps meet basic needs by providing staple food assistance and supplementary feeding programs (PMT). Second, it enhances environmental quality through infrastructure development, public facilities improvement, and increased community security. Third, it develops community skills by offering vocational training and job opportunities. Fourth, it boosts social participation by organizing community discussions and mutual cooperation activities (gotong royong). Fifth, it provides access to basic social services, such as operational support for integrated health posts (posyandu), BPJS payment assistance, and school supply assistance for children.